Environmental innovations: evidence from Brazilian manufacturing firms - Lucchesi, Andrea (2013)
The increasing concern with environmental damage and climate change has highlighted the importance of environmental innovations (EI) as an alternative to current technological standards. This thesis aims to contribute to the analysis of the determinants of environmental innovation and also to the identification of the effects of the adoption of environmental innovations on labor demand and performance of Brazilian manufacturing firms. Based on panel data between 1998 and 2008, the results obtained in Chapter 2 corroborate international evidence on the determinants of environmental innovation adoption. The environmental inducement hypothesis is verified, indicating that environmental regulation has an important role to influence the Brazilian firms in order to adopt both technical and organizational environmental innovations. Specifically related to developing countries innovative processes, our results confirm that foreign owned firms are significantly more likely to adopt \"green\" innovation, usually through capital embodied technology transfer and licensing agreements. The size of the firm and physical capital intensity are also important determinants of environmental innovation in Brazilian manufacturing firms. In Chapter 3 we use a translog cost function approach and we analyze the impact of environmental innovations on employment shares and wage bill shares in Brazilian manufacturing industries. The results obtained indicate that environmental technologies are unskilled biased, favoring blue-collar positions and wages, relative to white-collar ones. The \"green-collar\" jobs deriving from the green technologies adopted are in many situations (especially in low and medium technological intensive industrial sectors) filled by blue-collar workers, trained with green skills and thus capable of dealing with environmental preservation challenges. On the other hand, organizational environmental innovations registered a negative impact in blue-collar employment and wage bill shares, reinforcing the skill biased organizational change hypothesis, as the white-collar workforce is better prepared to deal with increased uncertainty, multi-tasking activities and increased responsibility. Concerning the effects of environmental innovation adoption on performance, Chapter 4 modeling strategy is based on a translog production function, due to its flexibility to represent different production structures, especially in the case of more than two factor inputs. The results indicate that both technical EI and organizational EI have positive impact on Brazilian manufacturing firms\' value added. We analyze four different types of technical EI in order to consider different characteristics of each type of EI, including those that reduce resources consumption and those that reduce environmental negative externalities, traditionally understood as additional compliance costs. All the different types of EI tested registered positive correlation with value added change. Pollution abatement investment was also tested and indicated positive effects on value added, even if to a lesser extent.